Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Multidimensional dissection of shared genetic susceptibility in ulcerative colitis and colorectal cancer: novel insights from integrative single-cell and multi-omics analysis - Fanfan Zhu; Xin Yao; Da Liu; Shanshan Wang; Xuyu Huang; Jing Zhou; Song Wang; Shanneng Tang; Dongping Lai; Shuang Yang; Xiaobing Meng; Xinyue Zhang; et al. (Inflammation Research, 2026)

Multivariable genome-wide analysis elucidates the shared genetic architecture, immunosenescence features, and gut-origin therapeutic targets of ulcerative colitis-associated multisystem inflammation - Shanneng Tang; Xin Yao; Shanshan Wang; Fanfan Zhu; Wenbin Zeng; Dongping Lai; Xiaobing Meng; Xinyue Zhang; Ziming Zhu; Tao Zhang; Ri’an Xu (Inflammation Research, 2026)

Synergistic coupling of micellar confinement and interfacial adsorption for fabricating high-density spherical nickel (II) tricarbohydrazide perchlorate - Jie-xin He; Dong-xu Zhang; Feng-yi Xia; Ri-lige Su; Bo-bo Lu; Jia-ni Xie; Zi-jie Bi; Qian-you Wang; Li Yang (Chemical Engineering Journal, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

CARE: a next-generation high resolution cloud and radiation remote sensing product and its Earth system applications - Husi Letu; Huazhe Shang; Run Ma; Chong Shi; Takashi Y. Nakajima; Hiroshi Ishimoto; Jérôme Riedi; Lesi Wei; Ri Xu; Dabin Ji; Qixiang Sun; Sude Bilige; et al. (Science Bulletin, 2026)

Temporal dynamics of microbial-soil particulate organic matter in response to nitrogen addition in an alpine steppe - Yilun Hu; Shang Wang; Qiuyu Chen; Ang Hu; Bin Niu; Xiang Chen; Ri Xu; Gengxin Zhang (Applied Soil Ecology, 2026)

Novel hapten design and highly sensitive monoclonal antibody–based immunochromatographic assay for benzo[a]pyrene in edible oil - Huan-Yuan Xu; Ri-Sheng Chen; Yu Wang; Yue-ming Chen; Sumed Yadoung; Surat Hongsibsong; Peiqiang Shuai; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

High-resolution imaging of plant delayed luminescence - Yan-Xia Liu; Hai-Yu Fan; Yu-Hao Wang; Yan-Liang Wang; Sheng-Wen Li; Shi-Jian Li; Xu-Ri Yao; Qing Zhao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Quantitative insights into osteocyte density developmental patterns in fossilized bone — A new method - Denis Horvath; Xu-Ri Wang; Martin Kundrát (Palaeoworld, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Evaluating waterbird migratory stopover habitat suitability in the Tumen River Estuary at the junction of China, North Korea and Russia using multi-source remote sensing imagery - Yang Liu; Jinhao Shi; Ri Jin; Weihong Zhu; Yue Guo; Baohua Guo; Xu Wang; Jingzhi Wang; Xiuxue Xia (Journal of Environmental Management, 2024)

Monoclonal antibody based colloidal gold immunochromatographic assay for the visual and rapid screening of profenofos - Ri-Sheng Chen; Jian-Cheng Yuan; Chong-Lan Luo; Yu Wang; Zi-Jian Chen; Ze-Shan Lin; Zhen-Lin Xu (Environmental Pollution, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Five previously undescribed compounds from Ajuga lupulina Maxim. and their in vitro activities - Kun-Jun Wang; Te-Ri-Gen Bao; Yong-Cheng Yang; Dong-Dong Wang; An-Hua Wang; Xiao-Xu Gao; Ting Yan; Jing-Ming Jia (Natural Product Research, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Re-examination of Dashanpusaurus dongi (Sauropoda: Macronaria) supports an early Middle Jurassic global distribution of neosauropod dinosaurs - Xin-Xin Ren; Shan Jiang; Xu-Ri Wang; Guang-Zhao Peng; Yong Ye; Lei Jia; Hai-Lu You (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Trophic Niche Partitioning of Five Sciaenidae Species Sampled in Zhoushan Archipelago Waters via Stable Isotope Analysis - Jing Wang; Ri-Jin Jiang; Yi Xiao; Rui Yin; Feng Chen; Yong-dong Zhou; Han-Xiang Xu (Frontiers in Marine Science, 2022)
Sciaenid fishes are usually associated with large freshwater inputs and are the most important economic fish on the coastal shelf off mainland China. To compare the differences in ecological niche and resource sharing among different populations of Sciaenidae species, we collected samples of Larimichthys polyactis , Collichthys lucidus , Johnius belangerii , Nibea albiflora , and Miichthys miiuy from Zhoushan Archipelago waters from 2019 to 2021 and investigated the carbon and nitrogen isotopic values in muscle tissues, the contribution of each food resource, and trophic niche widths and overlaps. Significant differences were observed in both isotopes in the muscles of the five Sciaenid species. Zooplankton was a key food resource for all Sciaenid species. In addition to zooplankton, J. belangerii , N. albiflora , and M. miiuy also fed on benthos organisms. C. lucidus presented a wide trophic niche width and had extensive habitat use. The trophic niche occupied by N. albiflora and M. miiuy was narrow; they presented a high trophic level, with a high degree of trophic niche overlap. This study showed that sciaenid fishes have overlapping trophic niches due to their common feeding on zooplankton, and differences in body size, migration, habitat, and feeding choices led to the reasonable sharing of resources among the five sciaenid fishes, allowing the coexistence of these species.

Zircon U–Pb ages and Hf isotopic compositions of two types of supracrustal rocks in the Northeastern Sulu UHP terrane: constraints on the surface boundary between South China and North China - Yang Xu; Ming-Ling Yang; Ali Polat; Kun-Guang Yang; Yuan-Ku Meng; Ri-Hui Li; Zhong-Bo Wang (International Geology Review, 2019)

Estimating N2O emissions from soils under natural vegetation in China - Xu-Ri; Yuesi Wang; Yinghong Wang; Haishan Niu; Yongwen Liu; Qianlai Zhuang (Plant and Soil, 2019)

Considerable methane uptake by alpine grasslands despite the cold climate: in situ measurements on the central Tibetan Plateau, 2008–2013 - Da Wei; Xu‐Ri; Tenzin‐Tarchen; Yuesi Wang; Yinghong Wang (Global Change Biology, 2015)
The uptake of CH 4 by aerate soil plays a secondary role in the removal of tropospheric CH 4 , but it is still highly uncertain in terms of its magnitude, spatial, and temporal variation. In an attempt to quantify the sink of the vast alpine grasslands (1 400 000 km 2 ) of the Tibetan Plateau, we conducted in situ measurements in an alpine steppe (4730 m) and alpine meadow (4900 m) using the static chamber and gas chromatograph method. For the alpine steppe, measurements (2008–2013) suggested that there is large interannual variability in CH 4 uptake, ranging from −48.8 to −95.8 μg CH 4 m −2 h −1 (averaged of −71.5 ± 2.5 μg CH 4 m −2 h −1 ), due to the variability in precipitation seasonality. The seasonal pattern of CH 4 uptakes in the form of stronger uptake in the early growing season and weaker uptake in the rainy season closely matched the precipitation seasonality and subsequent soil moisture variation. The relationships between alpine steppe CH 4 uptake and soil moisture/temperature are best depicted by a quadratic function and an exponential function ( Q 10 = 1.67) respectively. Our measurements also showed that the alpine meadow soil (average of −59.2 ± 3.7 μg CH 4 m −2 h −1 ) uptake less CH 4 than the alpine steppe and produces a similar seasonal pattern, which is negatively regulated by soil moisture. Our measurements quantified – at values far higher than those estimated by process‐based models – that both the alpine steppe and alpine meadow are considerable CH 4 sinks, despite the cold weather of this high‐altitude area. The consecutive measurements gathered in this study also highlight that precipitation seasonality tends to drive the interannual variation in CH 4 uptake, indicating that future study should be done to better characterize how CH 4 cycling might feedback to the more extreme climate.

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Plant and soil responses of an alpine steppe on the Tibetan Plateau to multi-level nitrogen addition - Yongwen Liu; Xu-Ri; Xingliang Xu; Da Wei; Yinghong Wang; Yuesi Wang (Plant and Soil, 2013)

Characterization of microsatellites in white croaker (Pennahia argentata) through cross species amplification of Miichthys miiuy - DIAN QIAO SUN; TIAN JUN XU; RI XIN WANG (Journal of Genetics, 2013)

Fourteen polymorphic microsatellite markers isolated from big-head croaker (Collichthys lucidus) - DIAN-QIAO SUN; BO ZHANG; TIAN-JUN XU; RI-XIN WANG (Journal of Genetics, 2013)

Genetic diversity and population structure of the marbled rockfish, Sebastiscus marmoratus, revealed by SSR markers - DIAN-QIAO SUN; GE SHI; XUE-ZHU LIU; RI-XIN WANG; TIAN-JUN XU (Journal of Genetics, 2013)

Wet precipitation chemistry at a high-altitude site (3,326 m a.s.l.) in the southeastern Tibetan Plateau - Bin Liu; Shichang Kang; Jimin Sun; Yulan Zhang; Ri Xu; Yongjie Wang; Yongwen Liu; Zhiyuan Cong (Environmental Science and Pollution Research, 2013)

Responses of CO2, CH4 and N2O fluxes to livestock exclosure in an alpine steppe on the Tibetan Plateau, China - Da Wei; Xu -Ri; Yinghong Wang; Yuesi Wang; Yongwen Liu; Tandong Yao (Plant and Soil, 2012)

Development of an electrochemical immunoassay for detection of gatifloxacin in swine urine - Jian Yi; Meng Meng; Zhong-qiu Liu; Jin-fang Zhi; Yuan-yang Zhang; Jing Xu; Ya-bin Wang; Jin-ting Liu; Ri-mo Xi (Journal of Zhejiang University-SCIENCE B, 2012)

Sequence and expression analysis of cathepsin S gene in the miiuy croaker Miichthys miiuy - Yue-na Sun; Tian-jun Xu; Jian-xin Wang; Yuan-zhi Cheng; Ri-xin Wang (Fish Physiology and Biochemistry, 2011)

The complete mitochondrial genome of bighead croaker, Collichthys niveatus (Perciformes, Sciaenidae): structure of control region and phylogenetic considerations - Tian-jun Xu; Yuan-zhi Cheng; Yue-na Sun; Ge Shi; Ri-xin Wang (Molecular Biology Reports, 2011)

A First Set of Polymorphic Microsatellite Loci from the Marbled Rockfish, Sebastiscus marmoratus - Tian-jun Xu; Xian-qing Quan; Yue-na Sun; Kuang-ci Zhao; Ri-xin Wang (Biochemical Genetics, 2010)

A comparison between measured and modeled N2O emissions from Inner Mongolian semi-arid grassland - Xu Ri; Yuesi Wang; Xunhua Zheng; Baomin Ji; Mingxing Wang (Plant and Soil, 2003)